Longitudinal Study of Metacognitive Skills and External Representation of Students in the Context of Problem-Solving - Ijirana Ijirana; Jusman Mansyur; Muh. Rizal; Sitti Aminah (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
This study aims to longitudinally describe the metacognitive skills and external representation in the context of problem-solving at Chemistry Education, Tadulako University. The qualitative study respondents were selected from a number of first year students for two consecutive semesters. Two respondents were selected based on results of selection using a metacognitive skills assessment questionnaire (MCAI) and we categorized as high and medium. Three problems were resolved by respondents at intervals of one to two weeks in each semester through a one-on-one thinking aloud and it was followed by a semi-structured interview. Data collection was recorded using a video camera. Metacognitive skills and external representation data from the odd and even semesters were deeply analyzed. This analysis technique was carried out by examining the results of problem solving and semi-structured interviews in detail and matching them with the indicators of metacogni-tive skills and external representation used by both respondents. The data analysis results showed that the thinking ability of respondents with high metacognitive skills in problem solving, experienced developments over time along with the development of their cognitive regulation and external representation. On the other hand, respondents with intermediate metacognitive skills during problem solving, were relatively the same for two consecutive semesters. Therefore, teachers need to consider the use of learning strategies by taking into account the number of students who have dominant characteristics in classroom learning, in terms of metacog-nitive skills and external representation.